Evolutionary Study of Bureaucracy Research From 2014 to 2024 - Satia Muharam, Riki; Afrilia, Ufa Anita; Komara, Syifa Rachmania (Sawala : Jurnal Administrasi Negara, 2024)
The aim of this study was to analyse the bibliographic characteristics and content of articles on Bureaucracy published in journals indexed by Scopus written by researchers from throughout the world. We conducted a bibliometric and content analysis of publication in the Scopus database. We only retrieved articles written in English. We conducted content analysis using the VOSviewer software and visualized the co-occurrence of keywords and bibliographic coupling of sources and countries. Following the study protocol, we found 1910 articles on Bureaucracy over the past 10 years. The most productive journal that published these articles was Research Handbook On Street Level Bureaucracy The Ground Floor Of Government In Context (n=26). The post productive country were United States (n=515). Based on cititations, The most influential document was Policy Implementation, Street-level Bureaucracy, and the Importance of Discretion with 316 citations. The keywords of research on Bureaucracy formed 6 clusters (e.g Bureaucracy, Human, Humans). From a global perspective, Bureaucracy research in the past one decades has increased significantly.